Answer:
Perimeter of ∆ABR = [tex] 12 + 2\sqrt{61} [/tex]
Step-by-step explanation:
Given, A(-2, -1), B(10, -1), and R(4, 4).
Perimeter of ∆ABR = [tex] \overline{AB} + \overline{BR} + \overline{AR} [/tex]
Distance between A(-2, -1) and B(10, -1) using distance formula:
[tex] \overline{AB} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} = \sqrt{(10 -(-2))^2 + (-1 -(-1))^2} [/tex]
[tex] \overline{AB} = \sqrt{(12)^2 + (0)^2} [/tex]
[tex] \overline{AB} = \sqrt{(144 + 0)} [/tex]
[tex] \overline{AB} = \sqrt{144} = 12 [/tex]
Distance between B(10, -1) and R(4, 4):
[tex] \overline{BR} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} = \sqrt{(4 - 10)^2 + (4 -(-1))^2} [/tex]
[tex] \overline{BR} = \sqrt{(-6)^2 + (5)^2} [/tex]
[tex] \overline{BR} = \sqrt{(36 + 25)} [/tex]
[tex] \overline{BR} = \sqrt{61} [/tex]
Distance between A(-2, -1) and R(4, 4):
[tex] \overline{AR} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} = \sqrt{(4 -(-2))^2 + (4 -(-1))^2} [/tex]
[tex] \overline{AR} = \sqrt{(6)^2 + (5)^2} [/tex]
[tex] \overline{AR} = \sqrt{(36 + 25)} [/tex]
[tex] \overline{AR} = \sqrt{61} [/tex]
Perimeter of ∆ABR = [tex] \overline{AB} + \overline{BR} + \overline{AR} [/tex]
Perimeter of ∆ABR = [tex] 12 + \sqrt{61} + \sqrt{61} [/tex]
Perimeter of ∆ABR = [tex] 12 + 2\sqrt{61} [/tex]